BUDAYA POPULER DI KALANGAN SANTRI PUTRI DALAM PERSPEKTIF FIKIH KONTEMPORER (STUDI KASUS DI KOMPLEKS “R2” PP. AL-MUNAWWIR KRAPYAK YOGYAKARTA) - Nurul Hidayah (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
Nowadays popular culture has become trend among the societyin all classes and also for cottage “pesantren”. This article is the result ofpopular culture praxis in pesantren PP. Al-Munawwir building “R2”. Thepurpose of this research is to elaborate and to know the values of popular culture among women santri and the receipt of causative factors of popular culture among the students. The researcher uses qualiltative-phenomenology in the field. Triangulation is used to collect the data with several steps; observation, interview, and documentation. Based on the contemporer fiqh and maslahah, the result of the research can be concluded that the popular culture which happened among the women students at the building “R2” has values of maslahah covers three levels, they are: D}aruruyyah, H}ajiyyah, dan Tah}siniyyah. Furthermore, contemporer fiqh prespective can explain that popular culture which happened not exceeded from the limit and not over the maximum limit of ethics and roles that has been implemented by the pesantren.Keywords: Popular culture, santri, maslahah, and contemporer fiqh